2016
DOI: 10.1177/0021998316666335
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chemical treatment methods on the outdoor performance of waste textile fiber-reinforced polymer composites

Abstract: In this study, weathering effect on untreated textile fiber-reinforced polymer composites and the effect of different chemical treatments for better interfacial adhesion on the outdoor performance were investigated. Degradation of physical, mechanical, and chemical properties of textile fiber-reinforced polymer composites was evaluated through common chemical treatments such as maleated coupling, alkaline treatment, silane treatment, and alkali–silane treatment. Untreated and chemically treated textile fiber-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It was noted that after alkali treatment the percentage of water absorption of bagasse fibre composite was enhanced owing to exposure of more surface area with more hydroxyl groups to absorb more moisture. On comparing with untreated composite, the improved water uptake resistance of alkali treated cotton fabric/low-density polyethylene composites were reported by Bakkal et al [94]. Ja et al [79] reported a lower degradation in the mechanical properties of napier grass/polyester composites after 10 wt.% NaOH treatment.…”
Section: Chemical Treatmentsmentioning
confidence: 70%
See 1 more Smart Citation
“…It was noted that after alkali treatment the percentage of water absorption of bagasse fibre composite was enhanced owing to exposure of more surface area with more hydroxyl groups to absorb more moisture. On comparing with untreated composite, the improved water uptake resistance of alkali treated cotton fabric/low-density polyethylene composites were reported by Bakkal et al [94]. Ja et al [79] reported a lower degradation in the mechanical properties of napier grass/polyester composites after 10 wt.% NaOH treatment.…”
Section: Chemical Treatmentsmentioning
confidence: 70%
“…On comparing with untreated composite, the improved water uptake resistance of alkali treated cotton fabric/low-density polyethylene composites were reported by Bakkal et al. [94]. Ja et al.…”
Section: Remedies To Water Absorption Of Cfpcsmentioning
confidence: 72%
“…Bakkal et al. 163 examined the impact of weathering on untreated and treated cotton fabric-reinforced low-density polyethylene composites. 1 M (NaOH) solution was used for treatment by immersing cotton fabrics for around 5 h at atmospheric temperature.…”
Section: Effect Of Alkali Treatment Of the Properties Of Biocompositesmentioning
confidence: 99%
“…Generally, natural cellulose fillers like fibers and particles have a high moisture absorption tendency, which is one of the main factors affecting the overall properties of the natural cellulose fillers reinforced polymer composites [11,12]. Therefore, the usage of natural cellulose fibers as reinforcing agent has been limited by their weakness to moisture absorption due to their hydrophilic in nature.…”
Section: Introduction *mentioning
confidence: 99%